Eliciting Individual Discount Rates in Thailand: A Tale of Two Cities - Rochanahastin, Nuttaporn; Horayangkura, Shinawat (Asian Journal of Applied Economics, 2023)
This paper aims to elicit individual discount rates (IDRs) from Thai citizens living in urban and rural areas, using real monetary incentives in a lab-in-the-field setting. This research investigates the differences in the discount rates in two districts with different socioeconomic characteristics. One represents a rural agricultural society governed by a district administrative organization, while the other represents an urban industrialized society governed by a city municipality. The researchers also compare the results from three different elicitation methods and across five time-horizons. This paper provides three main insights. First, the elicited discount rates for people living in a rural society are significantly lower than for those living in an urban society. Second, the discount rates also vary across time horizons, suggesting different risk considerations with respect to those time horizons. Lastly, the paper also addresses an intertemporal experimental design issue that results should be indifferent between elicitation methods and finds procedural invariants between the choice and matching tasks.